The relevance gives education environmental at the context current - Pereira Almeida , Bernard (Seven Editora, 2023)
The degradation of the environment, currently, is constant and can be observed all around the world. Although nature is essential to human survival, concern for its preservation has been put aside. However, the destruction of the environment puts at risk the future From own beings humans and, taking knowledge from that, teachings turned The awareness of this issue become increasingly important. With that in mind, the gift study had as objective to introduce one analysis about The importance of teaching gives environmental education in schools as a way to train people who, in society, act in a critically and consciously in relation to the various environmental problems, striving to achieve preservation of quite environment. That analysis if He gave referent to the years old initials of Teaching Fundamental, period in which the child begins his motor, cognitive and social development. For such, started from a bibliographic review as a research methodology, through which it can collect necessary data for the elaboration of the study with a survey of theoretical sources. So you can conclude that the teaching of environmental education in the early years of elementary school is essential for in the future soften you impacts arising gives degradation environmental, then takes to the individuals, still at your childhood, information, knowledge and change in behavior, allowing them, still acquire more responsibility environmental, ethics and Social. DOI: 10.56238/pacfdnsv1-103